Tongue Pressure Changes Before, During and After Crib Appliance Therapy - BİREN, SİBEL (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2010)
Objective: To describe tongue pressure changes before, during, and after crib appliance therapy in mixed dentition open bite cases. Materials and Methods: A crib appliance was applied to each of the 13 patients in the study group. The control group consisted of six patients. Tongue pressures were measured using a diaphragm-type pressure transducer during rest position and swallowing in changing intervals for 12 months in both groups. Tongue pressures were performed on the upper first molar, upper and lower central incisors, and on the middle spur of the crib appliance. Results: In the study group, the initial resting tongue pressure on the upper molar increased after appliance insertion and was followed by a decreasing trend for 12 months. The resting tongue pressures on the upper and lower incisors remained lower than initial values at the end of 12 months. Swallowing pressures returned to initial values at the end of 12 months, and the changes were insignificant. The resting and swallowing tongue pressures on the middle spur of the crib appliance decreased gradually during the 10 months (P < .05). Pressure changes in the control group were insignificant for all measurements. Open bite values in the study group increased significantly by the end of 12 months. Conclusions: Measurements performed on the crib confirm the tongue adaptation to environmental changes. Resting tongue pressures at the 12th month remained lower than the initial values. These findings indicate adaptive behavior of the tongue to open bite closure and the new position of the ncisors. (Angle Orthod. 2010;80:533-539.)
Keywords: Tongue pressure; Open bite; Pressure transducer; Crib appliance; MUSCLE FORCES; POSITION; CHEEK; FORM; LIP